Avaliação da aprendizagem de pacientes portadores de doença pulmonar obstrutiva crônica submetidos a um programa educativo - Souza, George Márcio da Costa e [UNIFESP] (2009)
Introduction: The education of chronic obstructive pulmonary disease – COPD patients is a fundamental part of pulmonary rehabilitation programs and it aims a better disease management. Objectives: To assess the learning capacity of COPD patients undergoing an educational program. Methods: A prospective study was performed with COPD patients at the Pulmonary Rehabilitation Center of the Universidade Federal de São Paulo/Lar Escola São Francisco, Brazil submitted to a educational program. Results: There was an increase in the number of correct questions to the questionnaire related to knowledge of the disease (59,58% to 91,25%; p < 0,001); a better performance in two activities of daily life (13,6% to 63,6%; p < 0,001 and 9,1% to 36,4%; p < 0,01). We observed a greater number of correct responses after the educational program; the mean went up from 6.5 ± 1.0 to 10.25 ± 0.96 (p = 0.002) when a pressurized nebulizer without a spacer was used, and from 6.7 ± 1.3 to 9.3 ± 0.9 (p < 0.001) when a nebulizer with a spacer was employed; the mean number of correct responses when using a dry powder inhaler increased from 8.9 ± 0.8 to 9.8 ± 0.2 (p < 0.001). We found no alterations in health quality or anxiety and depression levels. Conclusion: We concluded that a structured educational program acts as an important aid in treating COPD patients, providing them with essential knowledge about their disease and possibly leading to a change of improper health habits.